Morphological study of SnSb/Graphite composites influenced by different ratio of Sn:Sb - Kanyaporn Adpakpang (2018)
Experimental studies have shown that Sn/graphite nanocomposites are promising anodes for next generation rechargeable Li-ion batteries, as the graphite limits the volume expansions that Sn experiences upon Li-insertion. In order to provide further mechanical stability to the Sn a fabrication methods is described that allows for SnSb alloy in addition to pure Sn to attach on graphite matrices. In order to obtain an appropriate microstructure, in which the metal islands are dispersed equally throughout the matrix, the amount of Sn used in the reaction was varied between 10-40% while the Sb content was retained at 10%. Also to examine substrate effects three different graphites (artificial graphite, natural graphite and MCMB graphite) were used. The experimental process was carried out under the solution route in which NaBH4 and ethylene glycol were used as the reducing agent and solvent, respectively. Performing X-ray diffraction and electron microscopy revealed that the preferred SnSb phase with ratio Sn:Sb of 1:1 was obtained when the weight of the reactants was 10 wt.% of Sb, 20 wt.% of Sn, and 70 wt.% of artificial graphite. © 2012 Advanced Study Centre Co. Ltd.